Descriptions of pupae of two Hydropsyche species from China (Insecta, Trichoptera, Hydropsychidae) - Xie, Yue; Xu, Ji-Hua; Wang, Bei-Xin; Sun, Chang-Hai (Zootaxa, 2017)
Pupae of two Hydropsyche species collected from Zhe-jiang Province, China, were examined and their barcode sequences were generated and analyzed. The pupae of H. simulata and H. homunculus were associated with their adult males by mtCOI gene sequences, described, illustrated, and diagnosed.